4-Toluenesulfonyloxymethyl-(H)-phosphinate: A Reagent for the Introduction of O- and S-Methyl-(H)-phosphinate Moieties - Kostov, Ondřej; Páv, Ondřej; Buděšínský, Miloš; Liboska, Radek; Šimák, Ondřej; Petrová, Magdalena; Novák, Pavel; Rosenberg, Ivan (Organic letters, 2016)
The straightforward synthesis of sodium 4-toluenesulfonyloxymethyl-(H)-phosphinate and (H)-phosphinomethylisothiouronium tosylate as new reagents for the preparation of O- and S-methyl-(H)-phosphinic acid derivatives, respectively, is described. The reactivity of both reagents was demonstrated by the preparation of protected 2'-deoxyribonucleoside-O-methyl-(H)-phosphinates in the 5'- and 3'-series and 2',5'-dideoxyribonucleoside-5'-S-methyl-(H)-phosphinates. These compounds represent a new class of monomers compatible with the solid phase synthesis of oligonucleotides by H-phosphonate chemistry, as it was proved with the synthesis of a fully phosphonate heptamer.
Keywords: Phosphinic Acids; tosylové sloučeniny; indikátory a reagencie; Chemistry Techniques, Synthetic; Tosyl Compounds; kyseliny fosfinové; techniky syntetické chemie; Indicators and Reagents